Journalism and the Islamic Worldview: Journalistic roles in Muslim-majority countries. (4th May 2017) - Muchtar, Nurhaya; Hamada, Basyouni Ibrahim; Hanitzsch, Thomas; Galal, Ashraf; Masduki,; Ullah, Mohammad Sahid
Abstract : This paper looks at the extent to which journalistic culture in Muslim-majority countries is shaped by a distinctive Islamic worldview. We identified four principles of an Islamic perspective to journalism: truth and truth-telling ( siddiq and haqq ), pedagogy ( tabligh ), seeking the best for the public interest ( maslahah ), and moderation ( wasatiyyah ). A survey of working journalists in Africa (Egypt, Sierra Leone, and Sudan), Asia (Bangladesh, Indonesia, Malaysia, Oman, Qatar, Turkey, and the United Arab Emirates), and Europe (Albania and Kosovo) found manifestations of these roles in the investigated countries. The results point to the strong importance of an interventionist approach to journalism—as embodied in the maslahah principle—in most societies. Overall, however, journalists' roles in Muslim-majority countries are not so much shaped by a distinctively Islamic worldview as they were by the political, economic, and socio-cultural contexts.